AI ethics principles meet information governance principles : what to learn - Kultanen, Joni (2020)
This thesis takes an artificial intelligence (AI) ethics research framework and aims to identify information governance principles which could be used to further develop the research framework. Literature review is conducted in the field of information governance principles, and the field is identified to be very well-established and dominated by one set of generally accepted information governance principles. Instead of making suggestions on how to use the found information governance principles in further developing the AI ethics research framework, suggestion is made to use the information governance principles either partially for legislation or regulations on AI systems, or to utilize it fully in building AI governance on its foundation.